Periodontal Health Status Of 8-12 Year School Going Children - A Retrospective Study - MAHTANI, ANISHA A; JEEVANANDAN, GANESH; JAIN, RAVINDRAKUMAR (The journal of contemporary issues in business and government, 2021)
This study aimed to evaluate the periodontal health status of 8-12-year-old school going children. A retrospective study was conducted amongst 2736 school going children aged 8- 12 years reporting to a dental hospital in Chennai for treatment from June 2019 to March 2020. Digital case records of 2736 children were reviewed and the data was extracted. Data analysis was done using IBM SPSS Software Version 20.0 to run Chi square tests. The results revealed the overall prevalence of gingivitis amongst the 8-12 year old children to be 53.7% with 0.3% having periodontitis and 46% of children with clinically healthy gingiva. The study also found a significant relation between the diagnosis of periodontal health and age of the patients with p<0.001. No relation was established between gender and state of periodontal health.The study found the percentage of gingivitis to be 53.7% and periodontitis to be 0.3% in 8-12-year-old school going children.